The Economics of Sharecropping: A Study of Two Tarai Villages of Nepal - Acharya, Ram N. (1993)
The issue of resource allocation under share tenancy system has always been a fruitful source of controversy in economic literature. The Marshallian economists believe that the share tenants apply variable inputs less intensively than the fixed rent tenants or owner operators while the Cheungian economists argue that there would be no difference in input intensity across the tenure systems. This study examines the empirical validity of these two approaches,using evidence from the two tarai villages of Nepal. In particular, this study examines the differences in input and output intensities among three different types of plots of the paddy farmers -- owned (A) and shared (B) plots of mixed share tenants and shared (C) plots of pure share tenants -- for three different cases i.e., A-B, A-C and C-B. Mixed share tenants are farmers who rent in land besides cultivating own land. Pure share tenants are farmers who rent in land with no land of their own.The significance of these differences in input and output intensities were measured by employing two test procedures. An F-test based on Hotelling's T2 statistic was employed to measure the significance of differences in input and output intensities. The second test, which is based on Shaban's methodology, measures the impact of tenancy on input and output intensities by isolating the pure tenancy effect from the total variation in input and output intensities. Shaban's methodology was modified to in corporate two new variables, variety of paddy and plot size, in the model. The findings of the study reveal that the total differences in input and output intensities are partly explained by the differences in plot specific characteristics and partly by tenancy effect. Among the plot specific characteristics, plot size is found to be the most important variable in accounting for the differences in input and output intensities. The results of the study also indicate that the share tenants (plots B and C) apply inputs less intensively than the owner operators (plot A). within sharecropping, the pure share tenants (plot C) use more non-shared inputs compared to the mixed share tenants (plot B). After accounting for the impact of plot size, soil quality and the variety of paddy, the impact of sharecropping is to use lower inputs and produce lower output. The impact of sharecropping is highly significant, especially in the case of non-shared inputs such as compost, bullock power and family labour. These findings support the Marshallian school in the sharecropping controversy. This is consistent with Shaban's conclusion.